(untitled) (AYUSHDHARA, 2020)
Ayurveda emphasises on maintaining the healthy life and curing the disease of diseased. Various Siddhantas (Principles) have been mentioned in Ayurveda Treatise. Shatpadartha is one among the Siddhantas which hold basis for Dhatusamyata (equilibrium in bodily humours). Guna (attributes) is one amongst Shatpadartha explained in classical texts, which is Nischestyaa (inactive) remains with Samvayi Sambandha (inseparable relation) in Dravya. Acharya Charaka has enlisted 41 Guna and classified them into Sartha Guna, Paradi Guna, Gurvadi Guna and Prayatnadi Guna. Trisutra Ayurveda shows marked relation with Guna Siddhanta. The concept of Guna Siddhanta forms an underlying source of principles in practice to infer the Trisutra i.e. Hetu (Etiological factors), Linga (Symptoms) and Aushada (Treatment). The present article aims to confer the clinical understanding of Guna Siddhanta based on Samhita to provide an insight by Hetu, Linga, Aushada and bring about Dhatusamyata.